2016
DOI: 10.1016/j.physbeh.2016.06.033
|View full text |Cite
|
Sign up to set email alerts
|

Effects of predator odour on antipredator responses of Nile tilapia

Abstract: Several fish species exhibit antipredator responses when exposed to chemicals which indicate risk of predation. One such substance is the scent of a predator (a kairomone) that may induce defensive responses in a potential prey. In the present study, we show that chemical cues (odour) from predator fish induce antipredator and stress responses in Nile tilapia. When exposed to predator odour, Nile tilapia decreased activity and increased ventilation rate (VR), but no increase in plasma levels of cortisol and gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 78 publications
0
9
0
Order By: Relevance
“…In experiment two, the sociability of the O. amphimelas pair was unaffected by the presence of O. niloticus, and there was little evidence for a difference in activity between stimulus and control trials. Under the risk of potential predation, reduced activity (Sanches et al 2015;Miyai et al 2016;Ioannou et al 2017) and increased sociability (Ioannou 2020;Romenskyy et al 2020) are known behavioural responses, however neither were observed in this experiment when the stimulus chamber contained the O. niloticus. This niloticus through avoidance behaviours.…”
Section: Discussionmentioning
confidence: 53%
“…In experiment two, the sociability of the O. amphimelas pair was unaffected by the presence of O. niloticus, and there was little evidence for a difference in activity between stimulus and control trials. Under the risk of potential predation, reduced activity (Sanches et al 2015;Miyai et al 2016;Ioannou et al 2017) and increased sociability (Ioannou 2020;Romenskyy et al 2020) are known behavioural responses, however neither were observed in this experiment when the stimulus chamber contained the O. niloticus. This niloticus through avoidance behaviours.…”
Section: Discussionmentioning
confidence: 53%
“…To assess the swimming activity, I put a grid design on the back wall of the aquarium that had nine identical quadrants and quantified the frequency of quadrants changes (Barreto et al 2010;Miyai et al 2016). The presence of an animal in one quadrant was scored considering the bigger part of a fish body that was inside a quadrant.…”
Section: Fish Behaviormentioning
confidence: 99%
“…In vertebrates, the primary response to stress is a rapid elevation in glucocorticoids (such as cortisol or corticosterone), which quickly releases glucose into the blood priming the body for increased activity if required (secondary stress response) [ 43 ]. As such, olfactory cues of risk have been shown to alter the behaviour and physiology in fishes [ 44 , 45 ]. For instance, risk cues have been shown to increase cortisol concentrations and induce defensive behaviours in zebrafish ( Danio rerio ) [ 46 ], likely in anticipation of an imminent threat.…”
Section: Introductionmentioning
confidence: 99%